INTEGRASI STRATEGIS PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM OPERASIONAL SATUAN PENDIDIKAN SEBAGAI UPAYA PERSONALISASI PENDIDIKAN DI SEKOLAH DASAR - Ni Kadek Depi Dumaini; Gusti Ayu Nanik Ardhiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research analyzes the synchronization of differentiated learning strategies within the School Operational Curriculum (KOSP) at the elementary school level to support educational personalization. Although Kurikulum Merdeka offers high flexibility, its implementation often remains trapped in administrative formalities. This study employs a qualitative descriptive-analytical approach, collecting data through in-depth interviews with principals and teachers, as well as KOSP documentation analysis. The results reveal a